Assessing the effectiveness of governance strategies in the United Nations: The East Timor case - Gouveia, Ana Rita Palma (2023)
Assessing the Effectiveness of Governance Strategies in the United Nations: The East Timor Case explores multiple aspects of governance within the United Nations, focusing on the challenges faced, the strategies employed, and the resulting impact during the establishment and intervention of the peacekeeping mission in East Timor. Considering theories of international relations, effective governance in international organizations and in peacekeeping missions, and considering the Charter of the United Nations, as well as the decisions of the General Assembly and the Security Council, the present dissertation seeks to correlate all these elements and, through them, tries to assess the effectiveness of governance strategies. In a study grounded by the examination of theory in light of reality, it investigates specific areas such as accountability, democratic principles, human rights protection, participation, and transparency within the United Nations’ decision-making processes and institutional framework, and additionally examining the role of civil society, international cooperation, and member states in effective governance practices. It aims to contribute to a more extensive literature regarding governance issues and strategies, through the correlation of all the mentioned components, and holds the central argument that the peace operation in East Timor, from 1999 to 2001, reflected a series of attributes and principles related to effective governance.